A Comparative Analysis and Classification of TCP Solutions for MANET - Thilaka, A; Devi, V. Uma (International Journal of Computer Sciences and Engineering, 2025)
Mobile-Ad hoc networks are qualify by a lack of infrastructure, and by a random and quickly varying network topology; thus the need for a rich dynamic routing protocol that can adapt such an environment. In general, with the high mobility environment and high load network traffic, network performance perhaps took down causing packet loss or increase overhead. TCP optimization in mobile ad hoc networks MANETs is a challenging issue because of some unequaled characteristics of MANETs. Packet losses in MANETs are primarily due to congestion and frequent link losers but in case of wireless networks packet losses are accruing mainly due to congestion. Aims of this article is to Comparative analysis of transport layer perspective, it is very important to regard Transmission Control Protocol (TCP) as well for MANETs because of its broad application, and also demonstrates the several parameters comparison of Transmission Control Protocols solutions for Mobile ad-hoc wireless network